Designing Digital Solutions for Preserving Penan Sign Language: A Reflective Study - Tariq, Zaman; Alvin Wee, Yeo; Geran, Jengan (Hindawi Publishing Corporation, 2016)
Oroo’ is a language of nomadic Penans in the rainforests of Borneo and the only way of asynchronous communication between nomadic groups in the forest journey. Like many other indigenous languages, the Oroo’ language is also facing imminent extinction. In this paper,we present the research process and reflections of amultidisciplinary community-based research project on digitalizing and preserving the Oroo’ sign language. As a methodology for project activities, we are employing Participatory Action Research in Software Development Methodology Augmentation (PRISMA). Preliminary results show a general interest in digital contents and a positive impact of the project activities. In this paper, we present scenario of a research project that is retooled to fit the need of communities, informing language revitalization efforts and assisting with the evolution of community-based research design.